Systematic Literature Review; Peran Bimbingan dan Konseling Islam dalam Penanganan Kasus Bunuh Diri pada Remaja - Septiyani, Septiyani; Rohmatullah, Niam; Waki, Ahmad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
In 2018, Indonesia recorded 2,992 suicide cases, with adolescents and the elderly being the most affected groups. The 2022 I-NAMHS data revealed that 1.4% of adolescents had suicidal thoughts, 0.5% planned suicide, and 0.2% attempted suicide. Despite counselors being a profession that directly interacts with adolescents, discussions about the role of Islamic guidance and counseling in adolescent suicidal behavior are still very limited. Therefore, this study was conducted to reveal the role of counselors in adolescent suicide cases. This study employed a qualitative method with a systematic literature review approach. Journal searches were conducted through Publish or Perish, resulting in 369 journals, with 66 journals from Scopus, 103 journals from PubMed, and 200 journals from Google Scholar. After filtering using Covidence, 25 journals were selected for analysis. The results indicated that in handling suicide cases, counselors act as Suicide Gatekeepers.